Pancasila sebagai dasar moral dalam menegakkan hak atas pendidikan di indonesia - saputro, Muhtadi Amaludin (Maliki Interdisciplinary Journal, 2025)
Pancasila plays an important role as a moral foundation in realizing fair and equal education in Indonesia. The values of humanity and social justice in the second and fifth principles guide the government in ensuring the right to education for all citizens. This study uses a qualitative method through literature review related to the application of Pancasila values in education. The results show that Pancasila values have been implemented through several programs such as the 12-year compulsory education, Indonesia Smart Card (KIP), and character education in schools. However, challenges remain, such as unequal school facilities, a lack of teachers in remote areas, and limited learning infrastructure. Therefore, cooperation between the government, schools, and society is needed to strengthen the implementation of Pancasila values, so that education in Indonesia becomes fairer and accessible to everyone.